Daily Physical Activity in Children and Adolescents with Low Lumbar and Sacral Level Myelomeningocele - KURTEL, HIZIR; KARADAĞ SAYGI, NAİME EVRİM (TAYLOR & FRANCIS INC, 2021)
Purpose Children with low lumbar and sacral level myelomeningocele are expected to be community ambulators. However, they do not always meet the expected ambulation level by the time they reach adulthood. The purpose of this study is to investigate daily activity energy expenditure and physical activity levels of these patients in daily routine. Materials and methods 20 patients and 20 healthy peers were included in this case-control study. Omnidirectional accelerometer monitor was used for assessing activity energy expenditure, and daily durations spent in sedentary, light activity, and moderate to vigorous physical activity levels (NCT04186338). Results Mean activity energy expenditure and moderate to vigorous physical activity duration were significantly lower in the patient group, while age was positively correlated with sedentary time and negatively correlated with light activity time. Conclusions In patients with myelomeningocele, increasing daily activity energy expenditure and moderate to vigorous physical activity and, especially as age progresses, decreasing the sedentary behavior may assist in providing the expected ambulation level. These patients should be encouraged to partake in regular exercise programs.
Keywords: Energy expenditure; myelomeningocele; physical activity; sedentary behavior; SEDENTARY BEHAVIOR; ENERGY-EXPENDITURE; ASSOCIATIONS; AMBULATION; VALIDITY